PENGARUH UKURAN PARTIKEL BERAS HITAM (Oryza sativa L.) TERHADAP RENDEMEN EKSTRAK DAN KANDUNGAN TOTAL ANTOSIANIN - Maulida, Ria; Guntarti, Any (Pharmaciana, 2015)
Black rice has been tested for its high anthocyanin content. Black rice can be one of the potential sources of anthocyanin. Particle size is one of factors which influences amount of isolated  biocompound  in maceration process. Decreasing particle size can increase the amount of isolated  biocompound and extract yield value. The high value of extract yield shows effectiveness of maceration process. In this research, particle size variation has been done maceration process for investigating its influence on black rice extract yield and total anthocyanin content of maceration  result. This study used black rice ( Oryza sativa L.) from Beringharjo market, Yogyakarta. Maceration  with solvent of ethanol 96% add ed HCl 37% until pH 1,0(1:6) is done for 6 x 24 hours, with particle  size variation: mesh 20/40, 40/60 and whole bran of black rice. Data of extract yield and total  anthocyanin content are analyzed by using one-way ANOVA with confidence level 95%. The results  revealed that extract yield and total anthocyanin content of black rice extract with particle size  variation: mesh 20/40, 40/60 and whole bran of black rice intact 6%; 16%; 11,26%; and  30,76 mg/100  g; 1167,80 mg /100 g; 322,23 mg/100 g, respectively. There is significant difference  between  tested groups (P< 0,05). We concluded that particle size of black rice influences extract yield  and total anthocyanin content of maceration result.